2015
DOI: 10.3109/07357907.2015.1084002
|View full text |Cite
|
Sign up to set email alerts
|

Knocking down Dp71 expression in A549 cells reduces its malignancyin vivoandin vitro

Abstract: Dp71 is one of the most ubiquitously expressed isoforms of dystrophin, the pathological genes of DMD. In order to find whether the alteration of Dp71 can affect the phenotypes of cell other than PC12, an A549 cell line with stably transfected Dp71 siRNA plasmids was set up and named A549-Dp71AS cell. It is demonstrated for the first time that the A549-Dp71AS cell line displayed decreased invasion capabilities, reduced migration ability, decreased proliferation rate, and lessened clonogenic formation. Cisplatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…High DMD expression was also associated with poorer overall survival and shorter lymphocyte doubling time [17]. Other studies demonstrated that DMD Dp71 plays a central role in proliferation [6, 18], invasion and migration in vitro [18] and suppressed tumor growth in xenograft models [18]. Although the molecular mechanism underlying DMD over-expression and oncogenic activity is unknown, we suspect that it might be related to an increase expression of the Dp71 isoform.…”
Section: Discussionmentioning
confidence: 94%
“…High DMD expression was also associated with poorer overall survival and shorter lymphocyte doubling time [17]. Other studies demonstrated that DMD Dp71 plays a central role in proliferation [6, 18], invasion and migration in vitro [18] and suppressed tumor growth in xenograft models [18]. Although the molecular mechanism underlying DMD over-expression and oncogenic activity is unknown, we suspect that it might be related to an increase expression of the Dp71 isoform.…”
Section: Discussionmentioning
confidence: 94%
“…Cell viability was detected by Cell Counting Kit-8 (CCK-8, Beyond time, China), as previously described [ 12 ]. The assay was repeated 3 times.…”
Section: Methodsmentioning
confidence: 99%
“…Representative images of cells migrated into the wounds were captured and the length of the scratch was recorded and calculated 48 hr later. The results show that wound closure rate = (0 hr scratch width - 48 hr scratch width/0 hr scratch width ×100 [18]. …”
Section: Methodsmentioning
confidence: 99%
“…The bottom chamber contained 700 µl medium with 20 % FBS. After 24 h, the total numbers of the Transwell assay were imaged and the number of invasive cells was evaluated by measurement of absorbance measurement at 570 nm [18]. …”
Section: Methodsmentioning
confidence: 99%